Monitoring driver awareness through eye tracking - Chowdhury, Faiaz Hossain; Shetab, Muhtasim Al Buyes; Haque, Quazi Mohimenul; Ali, MD. Nazif (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.